Control Del Inventario En El Departamento De Bienes De La Empresa Cnel Ep U.N Los Ríos - Alvarado Rocafuerte, Karen Elizabeth (2019)
Through a public deed, the National Electricity Corporation CNEL S.A was created on December 15, 2008; and was integrated by the following electricity distribution companies: Bolívar SA, Regional El Oro SA, Regional Esmeraldas SA, Regional Guayas-Los Ríos SA, Manabí SA, Milagro CA, Los Ríos SA, Santo Domingo SA, Peninsula de Santa Elena SA and , Regional Sucumbíos SA (National Electricity Corporation, 2016) By Executive Decree No. 1459, issued on March 13, 2013, this entity was renamed the National Public Electricity Company CNEL EP, with the objective of providing electric power to all users in Ecuador. (National Electricity Corporation, 2016)